A Critical Review of “An illustrated English-Persian Dictionary of Prehistoric Archaeology” (Vol. 2) - Kourosh Roustaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This is a critical assessment of the second volume of the book An Illustrated English-Persian Dictionary of Prehistoric Archaeology, written by Seyed Mansour Seyed Sajadi. The book suffers from several shortcomings which have been discussed in detail, especially the ambiguities and wrong information of the entries. It is obvious that the sources of gathering information about the entries, especially those related to the Iranian archaeology, have been outdated. No mention of the new sites and regions explored in Iran during the last two decades is seen in the book. Even the information of classic sites, like Sarab and Sialk, excavated over thirty years ago, is, in most cases, superficial and incomplete. Almost all dates for the Iranian sites are wrong. There is little attention to the Iranian entries than they deserved. With several examples, it has been shown that the word “prehistoric” in the title of the book is nothing but a superficial endeavor to attract the readers. The frequency of wrong, vague, and incomplete information in the book is too high to be regarded as a reliable source of information for students.